PENGARUH PELATIHAN BERPIKIR POSITIF UNTUK MENURUNKAN KECEMASAN PADA MAHASISWA YANG SEDANG MENEMPUH SKRIPSI - rosma, sonya (EMPATHY Jurnal Fakultas Psikologi, 2013)
AbstractÂ This study aimed to determine the effectiveness of Positive Thinking Training Influence to Reduce the Students Anxiety Level in their final year. Subjects were students of Department of Information Faculty of Industrial Technology Ahmad Dahlan University class of 2008 who were doing his thesis. The method used was the experiment method. Data collection tool used was the anxiety scale. The analysis used in this study was the technique through independent sample t-test. The overall computational research data will be calculated using SPSS 19.0 for windows. Based on the results of t-test analysis obtained value of z = -3,442, p = 0.001, (p <0.05) it means that there is a decrease student anxiety levels after training given positive thinking. The majority of the study subjects before the training given with anxiety levels of medium category were as many as 10 subjects (100%), having been trained to think positively decrease anxiety by the five subjects (50%) included medium category, and 5 subjects (50%) included low category. Keywords: Positive Thinking Training, Anxiety.